Intervention of Anxiety Self-Therapy Education Media on Clients with Coronary Heart Disease (MD-TEMANKU/MD-MY FRIEND) - Heni Nurhaeni; Dinarti; Suryati; Joko Suwito (GoAcademica Research & Publishing, 2021)
This research affects the development of independent abilities of clients with coronary heart disease/CHD, in order to reduce the risk of severe occurrence of heart attacks at home due to anxiety with self-relaxation with Video MD-My Friend. This type of research design is an action research with video media, namely MD-My Friend., to 200 CHD clients in the community with a study period of 8 months, using heart rate measurements and anxiety instruments, and univariate analysis, to assess the characteristics of related variables. And bivariate analysis, continued with multivariate analysis on the influence of three meaningful variables. Based on the results of multivariate tests found that the age of the client of CHD affects knowledge, skills and self-recovery in CHD treatment on the application of MD-My Friend with P Value 0.001. Worsening of health conditions in coronary heart disease clients who are at risk 6 times with anxiety experienced. So it can be predicted that the risk of death from CHD cases will increase. As a physiological response that threatens a person's internal physiological state or psychological well-being, anxiety can intervene independently in a good and correct way. Therefore MD-My Friend as one of the alternatives to self-intervention in the Client CHD in order to be able to reduce his anxious condition, which also affects the condition of the CHD. MD-My Friend’s video has been shown to have an effect on knowledge, Skills and self-recovery are meaningful.